Dynamics of bioimpedance parameters during cardioversion in patients with atrial fibrillation - F. F. Bayramova; S. A. Zenin (Translational Medicine, 2026)
Background. Heart rate conversion during cardioversion has a mixed effect on the functional response of the cardiovascular system. According to impedance cardiography data, one month after electrical cardioversion, the most significant changes were in cardiac index, cardiac power index, total peripheral resistance, and total peripheral resistance index, exceeding echocardiographic parameters in sensitivity. These data suggest that bioimpedance cardiography is a useful and timely method for dynamically monitoring hemodynamic status in atrial fibrillation (AF). Objective. To assess hemodynamics in patients with atrial fibrillation after cardioversion, as well as to identify the real functional response of the cardiovascular system by analyzing bioimpedance indicators and ultrasound parameters of the heart. Materials and methods. To conduct a comparative analysis of hemodynamic parameters at baseline and one month later in 97 patients with persistent atrial fibrillation, followed by an assessment of the functional response of the cardiovascular system using two methods of bioimpedance cardiography and ultrasound diagnostics of the heart. Results. The study showed that the parameters measured by impedance cardiography did not change significantly, although the cardiac index, cardiac force index, total peripheral resistance, and total peripheral resistance index changed most clearly 1 month after cardioversion. Thus, the cardiac index changed from 2.93±1.25 to 2.64±0.99 l/min/m 2 at p=0.0001, the cardiac strength index – from 0.62±0.27 to 0.57±0.22 W/m 2 at p=0.0001, the total peripheral resistance – from 1536±736.97 to 1731±1515.6 din·s/cm 5 at p=0.0004, the index of total peripheral resistance increased from 3094±1464.3 to 3562±3709.9 din·s/cm 5 ·m 2 at p=0.0001. It is these indicators that reflect not so much the anatomical condition of the heart chambers, but rather the current organization of blood flow, the level of vascular load, and the ability of the cardiovascular system to operate in a more stable mode after the restoration of sinus rhythm. Echocardiographic indicators were less sensitive in the early stages, and after 6 months, only the peak blood flow velocity at the tricuspid valve showed significant changes (0.74±0.5 m/s to 0.64±0.4 m/s, p=0.028). The size of the right atrium changed from 4.21±0.7 cm to 4.01±0.71 cm at p=0.056, which indicates a positive trend, but does not reach the criteria of statistical significance. Conclusion. The obtained data allow us to consider bioimpedance cardiography as a useful and operational method of dynamic monitoring, which is not inferior to ultrasound examination of the heart in AF, and in a number of clinical situations, it detects functional changes earlier.